Presidential dissolution for the legislature - Chaibi, Abdeldjebar (Journal of Human Sciences, 2021)
The presidential dissolution of the national people’s assembly plays an important role in achieving political stability, if its objective reasons and practical justifications are realized, dictated by the supreme interest of the nation, it not only resolves the conflict between the government and the parliament, but also causes various conflicts that may arise between the constitutional authorities of the state. However, the release of the president’s hand in its use, because it is an exclusive discretion, can lead to undemocratic practices, which inevitably have legal effects on all political system.